(untitled) (Analele Universității București.Filosofie, 2025)
In this paper, I propose an interpretation for the semantics of intentionality, that Graham Priest uses in constructing his modal meinongianism, in “Towards Non-Being”. More precisely, I will take into account only the issue of existence, as a metaphysical notion. In this regard, my claim is that the monadic predicate of existence is not capable of constructing a full-fledged metaphysical notion of existence, or, differently said, it is not well equipped to account for all the modes of being that modal meinongianism implies. In trying to support my claim, I will use a strategy of reasoning, which employs a hierarchical conceptual structure, meaning that there are some first concepts, which determine the meaning for all the others. In this case, noneism is the primary notion, which imposes how other notions, such as modality and existence, will be defined. By using this way of reasoning, I will conclude that existence can be interpretated as world-dependable, meaning that the ontological nature of a world decides the ontological nature of the objects of its domain. In the pursuit of an argument for my thesis, I will begin with a short presentation of the core ideas of modal meinongianism. Afterwards, I will clarify the specific problems I am interested in and justify their necessity for being discussed. Lastly, I will formulate my argument, show its limits, and suggest a case of further research.